Formation and reactivity of inorganic and organic chloramines and bromamines during oxidative water treatment. (1st March 2017) - Heeb, Michèle B.; Kristiana, Ina; Trogolo, Daniela; Arey, J. Samuel; von Gunten, Urs
Abstract: The formation and further reactions of halamines during oxidative water treatment can be relevant for water quality. In this study, we investigated the formation and reactivity of several inorganic and organic halamines (monochloramine, N -chloromethylamine, N -chlorodimethylamine, monobromamine, dibromamine, N -bromomethylamine, N, N -dibromomethylamine, and N -bromodimethylamine) by kinetic experiments, transformation product analysis, and quantum chemical computations. Kinetic model simulations were conducted to evaluate the relevance of halamines for various water treatment scenarios. Halamines were quickly formed from the reaction of chlorine and bromine with ammonia or organic amines. Species-specific second-order rate constants for the reaction of chlorine and bromine with ammonia, methyl- and dimethylamine were in the order of 10 6 -10 8  M −1 s −1 . The formed halamines were found to be reactive towards phenolic compounds, forming halogenated phenols via electrophilic aromatic substitution (phenol and resorcinol) or quinones via electron transfer (catechol and hydroquinone). At near neutral pH, apparent second-order rate constants for these reactions were in the order of 10 −4 -10 −1  M −1 s −1 for chloramines and 10 1 -10 2  M −1 s −1 for bromamines. Quantum chemical computations were used to determine previously unknown aqueous p K a values, gas phase bond dissociation energies (BDE) and partial atomic charges of the halamines, allowing a better understanding of their reactivities. Kinetic model simulations, based on the results of this study, showed that during chlorination inorganic and organic chloramines are the main halamines formed. However, their further reactions with organic matter are outcompeted kinetically by chlorine. During ozonation, mainly inorganic bromamines are formed, since ozone quickly oxidizes organic amines. The further reactions of bromamine are typically outcompeted by ozone and thus generally of minor importance. The use of peracetic acid for saline ballast water treatment can result in the formation of substantial amounts of bromamines, which can react with dissolved organic matter and contribute to the formation of brominated products. Graphical abstract: Highlights: Novel rate constants for the formation and reactivity of several halamine species. Second-order rate constants for halamine formation are 10 6 –10 8  M −1  s −1 . Reactivity of bromamines with phenol is 10 2 –10 6 times higher than for chloramines. Reactivity of halamines can be linked to their physical-chemical properties. Model calculations show the relevance of halamines during oxidative treatment.